A new subspecies record for the flora of Turkey: Artemisia santonicum L. subsp. patens (Neilr.) K.M.Perss. (Asteraceae) - Kurşat, Murat; Türkoğlu, İsmail; Civelek, Şemsettin; Tabur, Selma (My University, 2011)
-
Keywords: Biyoloji